The Re-globalization Process in the Indian Ocean: the Ibadi Press in Zanzibar (al-Sultaniyya) - Beatrice Nicolini (Arabian Humanities)
During the XIX century, on the Zanzibar Island, a gradual process of osmosis occurred through the first publications that often linked magical practices with the precepts of the Quran, resulting in a social and political interpretation of the Omani power on the Eastern African island that reflected a multiplicity of cultural roots. The vast network of international trade links, and the presence of numerous mercantile communities were progressively consolidated, stretching from Africa, Arabia, the Gulf, and India as far as Southeast Asia, Indonesia and even China with Zanzibar as a polarizing new capital and centre. Modernity brought by the international presences in Zanzibar involved numerous complex reflections in order not to losing the traditional society values and the main Ibadi precepts inside the new-coming progresses. Ibadi press on Zanzibar Island was in fact representing one of these social and political objects: re-globalizing the ancient communication flows between Oman and East Africa.